Reading and Writing Skills in Adolescents With Autism Spectrum Disorder Without Intellectual Disability - Baixauli, Inmaculada; Rosello, Belen; Berenguer, Carmen; Téllez de Meneses, Montserrat; Miranda, Ana (Frontiers in Psychology, 2021)
The purpose of this study is to extend the knowledge about academic achievement in individuals with Autism Spectrum Disorder (ASD). To this end, first, we analyzed differences in a wide range of reading and writing skills in adolescents with ASD without intellectual disability (ASD-WID) and adolescents with typical development (TD). Second, these two groups were compared on academic outcomes in core subjects and indicators of successful transition to secondary school. Third, the potential contribution of literacy skills to academic outcomes was examined in the two groups. Participants were 56 adolescents between 12 and 14 years old, 30 with ASD-WID and 26 with TD. Results showed no significant differences between the two groups on measures of reading fluency or literal and inferential comprehension. However, the performance of the group with ASD was significantly lower on reading comprehension processes that assess cognitive flexibility. Regarding their written expression skills, significant differences were observed between the group with ASD and the group with TD on most of the indicators analyzed: productivity, lexical diversity, and overall coherence (resolution component). In addition, findings showed that the deficits in reading and writing observed in the adolescents with ASD significantly affected their academic achievement, which was lower than that of their peers with TD and below what would be expected based on their intellectual capacity. Moreover, their families' perceptions of the transition to high school reflected worse adjustment and lower self-esteem, confidence, and motivation.